2001
DOI: 10.1093/ajcn/74.5.650
|View full text |Cite
|
Sign up to set email alerts
|

Dietary treatment of iron deficiency in women of childbearing age

Abstract: In iron-deficient women of childbearing age, a high-iron diet produced smaller increases in SF than did iron supplementation but resulted in continued improvements in iron status during a 6-mo. follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 14 publications
(25 reference statements)
3
85
0
Order By: Relevance
“…Moreover, consumption of GLV was not associated with Hb level or prevalence of IDA probably due to the short recall period. Lack of significant changes in Fe intake even after supplementation of Fe for 9 months was attributed to inaccuracies and insufficient power to detect changes in dietary data (32) . Although lower intakes of micronutrient-rich foods like GLV, fruits and milk have been reported (19) in mothers from India, the social aspects associated with it have received little attention.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, consumption of GLV was not associated with Hb level or prevalence of IDA probably due to the short recall period. Lack of significant changes in Fe intake even after supplementation of Fe for 9 months was attributed to inaccuracies and insufficient power to detect changes in dietary data (32) . Although lower intakes of micronutrient-rich foods like GLV, fruits and milk have been reported (19) in mothers from India, the social aspects associated with it have received little attention.…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of IFA tablets is mostly influenced by age, socioeconomic status, community awareness regarding importance of IFA tablets. A study of Patterson et al, (2001) have suggested that a diet rich in iron appears to be more advantageous over iron supplementations as it is cost-effective and shows higher efficacy and benefits in the long-term. Dietary iron absorption depends on bioavailability of iron i.e.…”
Section: Iron Bioavailability: Notes From the Fieldmentioning
confidence: 99%
“…73 mmol/l, TFS , 20 %, Hb , 120 g/l, Ht , 37 %, MCV , 80 fl, MCHC , 300 g/l, MCH , 30 pg, CRP . 6 mg/l (15)(16)(17) .…”
Section: Anthropometric Datamentioning
confidence: 99%